STRATEGIC ADAPTATION TO MITIGATE CLIENT CHURN: A SMART STUDY OF AN INDONESIAN B2B DIGITAL MARKETING AGENCY - Okta Bhakti Nurangga (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study identifies the root causes of the business crisis experienced by MGDverse, an Indonesian B2B digital marketing consultancy serving MSMEs, and determines strategic adaptation options to improve business sustainability and performance. Research Methodology: A single-case study was conducted for the 2021–2025 period using qualitative diagnostic analysis and structured decision-making techniques. Porter’s Five Forces, 5 Whys Root Cause Analysis, SWOT/TOWS Matrix, and the Simple Multi-Attribute Rating Technique (SMART) were employed to diagnose organizational challenges, formulate alternatives, and prioritize strategic responses. Results: MGDverse experienced declining performance, reflected in an increase in monthly churn from 5.45% to 7.76%, a 23% reduction in active clients, a decline in net income margin from 26.57% to −2.70%, and a rise in COGS from 5.63% to 20.19%. Three root causes were identified: client-segment mismatch, client capability limitations beyond the firm’s service scope, and inadequate value communication. SMART ranked a Structured Client Success and Results Reporting System as the highest-priority strategy, followed by a Systematic Client Acquisition Pipeline, Tiered Service Packages, COGS Restructuring, and Creative Performance Service Expansion. Conclusions: The crisis was primarily associated with deficiencies in client alignment, expectation management, and value communication. Strengthening client success management emerged as the most effective response. Limitations: The findings are based on a single-company case study. Contributions: This study provides a practical framework for diagnosing business crises and prioritizing strategic adaptation in service-based organizations.